2020
DOI: 10.31744/einstein_journal/2020ao4662
|View full text |Cite
|
Sign up to set email alerts
|

Prostate volume measurement by multiparametric magnetic resonance and transrectal ultrasound: comparison with surgical specimen weight

Abstract: Prostate volume measurement by multiparametric magnetic resonance and transrectal ultrasound: comparison with surgical specimen weight Avaliação do volume prostático obtido por ressonância magnética multiparamétrica da próstata e ultrassonografia transretal comparado ao peso da peça cirúrgica

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…Foi encontrada correlação entre o peso prostático verificado pela ultrassonografia transretal e o PSA total pré-operatório dos pacientes (p=0,0195 e r=0,22), porém com força inferior à correlação positiva encontrada entre o primeiro e o volume prostático estimado pela RNM pélvica (p=0,0001 e r=0,71), situação similar à encontrada na literatura (MARTINS et al, 2020).…”
Section: Discussionunclassified
“…Foi encontrada correlação entre o peso prostático verificado pela ultrassonografia transretal e o PSA total pré-operatório dos pacientes (p=0,0195 e r=0,22), porém com força inferior à correlação positiva encontrada entre o primeiro e o volume prostático estimado pela RNM pélvica (p=0,0001 e r=0,71), situação similar à encontrada na literatura (MARTINS et al, 2020).…”
Section: Discussionunclassified
“…Subsequent studies confirmed that the TPV measured by TRUS is comparable with findings on multiparametric MRI and both have excellent agreement with real prostate weight of the surgical specimens. 12 , 13 However, TZV measurement on TRUS is operator dependent and its accuracy is controversial. 14 Some authors report significant discrepancies between TRUS determination of TZV when compared with enucleated adenoma weight.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate volume estimation on the basis or TRUS data was associated with the availability of these findings among all patients included into the study. In addition, recent investigations have proven that prostate volume measured by TRUS does perfectly correspond to the actual weight of a surgical specimen [14]. Ever since the prognosis and management differ according to the extent of tumor involvement, patients were categorized into localized (cT1-2N0M0, n=272), locally advanced (T3-4N0M0, T1-4N1M0, n=231) and metastatic PC (T1-4N0-1M1, n=211) groups.…”
Section: Methodsmentioning
confidence: 99%